(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Inhaling excessive amounts of Particulate Matter (PM) which can be blown over great distances by the wind and then settle in the ground, water, or in the air we breathe, can be hazardous to both sensitive and non-sensitive persons. The study investigates the mass concentration of particulate matter (PM) in Kano and Abuja. Utilizing a purple air sensor, PM1.0, PM2.5, and PM10.0 were all examined along with some climatic variables including temperature and relative humidity. In Kano and Abuja, monitoring took place between January 2021 and December 2021. Results indicate that the monthly PM exceeds the WHO 24-hour limit for the two locations. When the standard limit of the Air Quality Index (AQI) is taken into consideration, the mean value of PM2.5 shows that the air quality in both locations is dangerous for sensitive persons, such as those who have respiratory ailments while the mean value of PM10.0 shows that the air quality in both locations was moderate for both sensitive and non- sensitive person. The results in this study suggests that government should enhance its current air quality regulations and install new air quality sensors in sufficient locations in Nigeria so that additional research may be done on such regions. The results of a Pearson correlation analysis show that PMs and relative humidity have substantial negative correlations indicating that as relative humidity rises in either locations, PMs mass concentration would decrease as well. A relatively high correlation existed between PMs and temperature for both locations.